Invasive imaging modalities in a spontaneous coronary artery dissection: when “believing is seeing” - Mehmedbegović, Zlatko; Ivanov, Igor; Čanković, Milenko; Perišić, Zoran; Kostić, Tomislav; Maričić, Bojan; Krljanac, Gordana; Beleslin, Branko; Apostolović, Svetlana (Frontiers in Cardiovascular Medicine, 2023)
Spontaneous coronary artery dissection (SCAD) is a rare but increasingly recognized cause of acute coronary syndrome (ACS) with recent advancements in cardiac imaging facilitating its identification. However, SCAD is still often misdiagnosed due to the absence of angiographic hallmarks in a significant number of cases, highlighting the importance of meticulous interpretation of angiographic findings and, when necessary, additional usage of intravascular imaging to verify changes in arterial wall integrity and identify specific pathoanatomical features associated with SCAD. Accurate diagnosis of SCAD is crucial, as the optimal management strategies for patients with SCAD differ from those with atherosclerotic coronary disease. Current treatment strategies favor a conservative approach, wherein intervention is reserved for cases with persistent ischemia, patients with high-risk coronary anatomy, or patients with hemodynamic instability. In this paper, we provide a preview of invasive imaging modalities and classical angiographic and intravascular imaging hallmarks that may facilitate proper SCAD diagnosis.